A CRITICAL REVIEW OF TRADITIONAL WISDOM IN THE QURAN: EXPLORING THE VALUE OF SIRI’ IN SURAH YUSUF - Abdul Rahman Said, Rukman; Ilham, M.; Rusdi, Mikdar; Amiruddin, Muhammad Majdy (Jurnal Adabiyah, 2022)
Contextualizing one's comprehension of the Koran is sometimes accomplished through the use of local wisdom. Siri' is one of the wisdoms that are deeply ingrained in Indonesia, particularly in the Bugis Makassar population. This article attempted to decipher Siri's ideals as revealed in the Quran. This endeavor was accomplished by examining Surah Yusuf as the primary source of data, which waas supplemented with value theories gleaned from recent papers. The text of Surah Yusuf was then reduced to the necessary values and examined using content analysis. The study took a qualitative normative approach. This analysis discovered that Surah Yusuf verses 23-25 include the value of siri. This principle manifests itself in Prophet Yusuf's efforts to preserve his honor following his seduction by Zalikha. ملخّص إن الفهم السياقي للقرآن في بعض الأحيان يتم من خلال إيجاد صلة بين المقاصد الكلية للقرآن وبين الحكمة المحلية. سيري هو إحدى المصطلحات التي تم غرسها في المجتمع الإندونيسي خاصة البوقيس-المكاسر. وهي تعني نظام القيم الثقافية والإجتماعية في الدفاع عن كرامة الإنسان كفرد أو مجتمع. كان الغرض من هذا البحث هو فهم مبدأ سيري كما ورد في القرآن الكريم. وذلك من خلال تقييم سورة يوسف كمصدر رئيسي للبيانات والتي تم استكمالها بنظريات القيم المستمدة من أحدث البحوث والمقالات. وبعد ذلك تم تقليص سورة يوسف وفقا للقيم ذات الصلة وتحليلها بطريقة تحليل المحتوي. وهذا البحث تم تصميمه بنهج معياري نوعي. ووجدت نتائج البحث أن قيمة سيري واردة في سورة يوسف الآيات: 23-25. وهذه القيمة هي من خلال جهود النبي يوسف عليه السلام للحفاظ علي شرفه عندما تلقي الإغواءات من زليخة.